Experience in researching the identity of active internet users - Viktoriya A. Peregudina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper reflects the results of a study aimed at studying the features of the identity of the personality of active users of network mass media of young age. The research is based on the idea of modern authors that identity on the Internet is one of the aspects of real identity that arises due to the projection of stable, significant personal characteristics into the virtual world, the use of the possibilities of information and communication technologies to construct new ones, as well as the transformation of existing aspects of personal identity. To compare the aspects of the identity of the personality of active Internet users (I-virtual, I-ideal and I-real), the criteria of differentiation of existing images, the multiplicity of created Self-images, as well as the degree of fullness and development of specific aspects of identity are used. The degree of differentiation of the types of identity real and virtual-was diagnosed based on the analysis of the results of Osgoods semantic differential; the indicator of the multiplicity of Self-images presented in reality, as well as in virtual space, was measured using the Kuhn-McPartland test Who I am? and its modification Who I am online?; the variability of real personality traits in the aspect of virtual self-presentation was diagnosed by comparing the results of the individual typological questionnaire (ITO) and the method of diagnosing interpersonal relations (DMO) by L. N. Sobchik. As a result of the analysis using theoretical and empirical research methods, as well as data processing methods (descriptive statistics, graphical analysis and calculation of criteria for differences and correlation), it is proved that the identity of the personality of active Internet users is characterized by a greater multiplicity of Self-images, less differentiation of the Self-concept (the image of the virtual Self merges with the image of the real Self), as well as a pronounced tendency to variability of personal characteristics due to an increase in the severity of socially desirable personality traits and a tendency to aggravity of existing ones.